Análise jurídica do pagamento por serviços ambientais no Estado do Amazonas: REDD+ como instrumento de promoção do desenvolvimento sustentável - Santos, Vanylton Bezerra dos (2010)
The environment is undergoing profound changes, arguably resulting from human activities. The exploitation of natural resources for production as well as the accumulation of waste from the consumer, has placed a limit on production capacity and cycling on the planet. In mitigation of this problem, play a key role and the right environmental policies. The command and control policies, despite being the main way in an attempt to conserve the environment, has not achieved the desired efficiency. This has led mankind to think of other ways to solve the environmental problem. Programs Payment for Environmental Services (PSA) are an extremely valuable option because they are easily suited to capitalist logic. Payment (as monetary or non-monetary) in exchange for actions that demonstrably influence the maintenance or improvement of an ecosystem service is considered one of the most effective ways to conserve the environment. PSA, an environmental-economic instruments already implemented in many countries, is one of the environmental policies of the State of Amazonas, since 2007. Titled Forest Scholarship Program (GMP), the PSA program, Amazon is implemented as Reducing Emissions from Deforestation and Forest Degradation (REDD). This program, whose bases are environmental, economic and social aims to combat climate change caused by deforestation, promoting sustainable development within the protected areas of Amazonas state, through financial and social incentives. Keywords: Economic and Environmental Law. Payment for Environmental Services. Reducing Emissions from Deforestation and Forest Degradation. Bolsa Floresta Program. Sustainable Development.